Bio-inspired flat optics for directional 3D light detection and ranging - Clément Majorel; Amir Loucif; Emil Marinov; Renato Juliano Martins; Adelin Patoux; Pierre-Marie Coulon; Virginie Brandli; Michel Antolovic; Claudio Bruschini; Edoardo Charbon; Patrice Genevet (npj Nanophotonics)
Abstract The eyes of arthropods, such as those found in bees and dragonflies, are sophisticated 3D vision tools that are composed of an array of directional microlenses. Despite the attempts in achieving artificial panoramic vision by mimicking arthropod eyes with curved microlens arrays, a wealth of issues related to optical aberrations and fabrication complexity have been reported. However, achieving such a wide-angle 3D imaging is becoming essential nowadays for autonomous robotic systems, yet most of the available solutions fail to simultaneously meet the requirements in terms of field of view, frame rate, or resistance to mechanical wear. Metasurfaces, or planar nanostructured optical surfaces, can overcome the limitation of curved optics, achieving panoramic vision and selective focusing of the light on a plane. On-chip vertical integration of directional metalenses on the top of a planar array of detectors enables a powerful bio-inspired LiDAR that is capable of 3D imaging over a wide field of view without using any mechanical parts. Implementation of metasurface arrays on imaging sensors is shown to have relevant industrial applications in 3D sensing that goes beyond the basic usage of metalenses for imaging.